Análisis de la comercialización de la Empresa Dolupa C.A. sucursal Daule durante el periodo de pandemia - Pin Valarezo, Jose Robert (2024)
The following research project will study and analyze how the company DOLUPA C.A. faced the pandemic process during the period of 2020 and 2021. The company under consideration for this marketing analysis is one of the most renowned in the Ecuadorian coast due to its seventy-one years of history since its foundation in the city of Guayaquil. The company is dedicated to the production and commercialization of cakes and snacks. The pandemic process caused by the COVID-19 virus in the country is one of the historical events that Ecuador has experienced to date. It revealed that the sectors responsible for handling this type of crisis were not adequately prepared to face the severity of the pandemic, resulting in adverse effects on other important sectors of the country..............